2022
DOI: 10.1038/s41598-022-15523-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity patterns of students from primary to secondary school: a 5-year longitudinal study

Abstract: This study aimed to annually examine anthropometric characteristics and physical activity (PA) among children transitioning from fourth grade (9–10 years of age) to eighth grade (13–14 years of age) in Japan. The participants’ (n = 63) age, grade, sex, weight, height, and weight status were recorded at baseline. Accelerometry assessments were performed annually following established protocols. Time spent on activities requiring ≥ 3 metabolic equivalents (METs), 1.6–2.9 METs, and ≤ 1.5 METs were defined as mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Overall, based on inconsistent findings, we found inconclusive evidence for a change in TPA, LPA, MVPA and active transport of adolescents across the transition from primary to secondary school. Sedentary behaviour SB was assessed using accelerometers (22,36,(54)(55)(56)59,60,64) and questionnaires (53,55,57,58,60) . Three studies received a strong methodological quality rating (54,56,64) , and one study received a strong methodological quality rating for the accelerometer-based data and a moderate quality rating for the questionnaire-based outcomes (55) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, based on inconsistent findings, we found inconclusive evidence for a change in TPA, LPA, MVPA and active transport of adolescents across the transition from primary to secondary school. Sedentary behaviour SB was assessed using accelerometers (22,36,(54)(55)(56)59,60,64) and questionnaires (53,55,57,58,60) . Three studies received a strong methodological quality rating (54,56,64) , and one study received a strong methodological quality rating for the accelerometer-based data and a moderate quality rating for the questionnaire-based outcomes (55) .…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary behaviour SB was assessed using accelerometers (22,36,(54)(55)(56)59,60,64) and questionnaires (53,55,57,58,60) . Three studies received a strong methodological quality rating (54,56,64) , and one study received a strong methodological quality rating for the accelerometer-based data and a moderate quality rating for the questionnaire-based outcomes (55) . Six studies received a moderate methodological quality rating (22,36,(57)(58)(59)(60) , and one study received a poor quality rating (53) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 81% of children worldwide are physically inactive 11 . Moreover, longitudinal studies have revealed that decreased physical activity and increased sedentary behavior during childhood and adolescence [12][13][14] . Concerns remain regarding the adverse effects on healthy brain development and cognitive function in children.…”
Section: Introductionmentioning
confidence: 99%